1978
DOI: 10.4319/lo.1978.23.6.1214
|View full text |Cite
|
Sign up to set email alerts
|

Sessile bacteria: An important component of the microbial population in small mountain streams 1

Abstract: Direct counts by epifluorescence microscopy demonstrated that cpilithic bacteria were numerically more important than fret-floating bacteria in unpolluted mountain streams. Concentrations of sessile bacteria associated with the upper surfaces of submerged rocks coincided with fluctuations in epilithic algal biomass. Electron microscopy of thin-section prcparations of natural samples showed that the attached algae provided a surface for bacterial colonization.This close physical relationship between the bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
175
1
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(187 citation statements)
references
References 0 publications
9
175
1
2
Order By: Relevance
“…tracellular polymer production has been observed in aquatic (mostly freshwater) systems (Paerl 1974(Paerl , 1978Geesey et al 1978;Christensen et al 1985), but information on the polymer-producing organisms and the composition of the polymers is limited. Hobbie and Lee (1980) suggested that extracellular polysaccharides are more abundant than bacteria in sediments and may be an important food source for macrobenthos.…”
Section: Discussionmentioning
confidence: 99%
“…tracellular polymer production has been observed in aquatic (mostly freshwater) systems (Paerl 1974(Paerl , 1978Geesey et al 1978;Christensen et al 1985), but information on the polymer-producing organisms and the composition of the polymers is limited. Hobbie and Lee (1980) suggested that extracellular polysaccharides are more abundant than bacteria in sediments and may be an important food source for macrobenthos.…”
Section: Discussionmentioning
confidence: 99%
“…The bulk of microbial biomass in headwater streams is associated with sediment biofilms (Geesey et al 1978) that consist of extracellular polymeric substances (EPS) containing bacteria, to some extent fungi and sometimes also algae (Lock 1993). The heterotrophic biofilm microorganisms commonly satisfy their energy and carbon demand from dissolved organic carbon (DOC) that is immobilized from the porewater by the EPS matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Most contemporary biofilm research rests on the discovery made more than 35 years ago by Maurice Lock, Gill Geesey and Bill Costerton: bacteria attached to surfaces dominate microbial life in streams [1][2][3] . These microbiologists pioneered research into stream biofilms, also termed periphyton or epilithon, and described them as complex aggregates of bacteria, algae, protozoa, fungi and meiobenthos.…”
mentioning
confidence: 99%